Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: Is y – x positive? (1) y > 0 (2) x = 1 – y [#permalink]

Show Tags

28 Oct 2010, 18:58

yamikikyou wrote:

Statement 1 doesn't give you anything b/c you don't know anything about x.

Statement 2 isn't sufficient alone either: x = 1 – y ; 5 = 1 - (-4); y - x is negative x = 1 – y ; -5 = 1 - 6; y - x is positive

Both statements together is also insufficient, b/c x = 1 – y ; 1/2 = 1 - 1/2; y - x = 0

So I think the answer should be E.

could you please explain the combined equation in detail by method of substitution, yeah, i could figure out that both the statements are not sufficient individually and when combined, gives an equation X+Y=1 and Y>0 .....iam not able to get a "no" for this equation

Re: Is y – x positive? (1) y > 0 (2) x = 1 – y [#permalink]

Show Tags

28 Oct 2010, 23:54

satishreddy wrote:

yamikikyou wrote:

Statement 1 doesn't give you anything b/c you don't know anything about x.

Statement 2 isn't sufficient alone either: x = 1 – y ; 5 = 1 - (-4); y - x is negative x = 1 – y ; -5 = 1 - 6; y - x is positive

Both statements together is also insufficient, b/c x = 1 – y ; 1/2 = 1 - 1/2; y - x = 0

So I think the answer should be E.

could you please explain the combined equation in detail by method of substitution, yeah, i could figure out that both the statements are not sufficient individually and when combined, gives an equation X+Y=1 and Y>0 .....iam not able to get a "no" for this equation

Combined, y>0 and x+y=1. When problem doesn't state that the variables are integers, you must consider fractions.

if y is 1/4 then x is 3/4 therefore x>y false if y is 3/4 then x is 1/4 therefore x<y true

So combined, it is insufficient.
_________________

Consider KUDOS if my post was helpful.

My Debrief: http://gmatclub.com/forum/750-q49v42-105591.html#p825487

(1) y > 0. Clearly insufficient, as no info about x.

(2) x = 1 – y --> \(x+y=1\) --> the sum of two numbers equals to 1, we can not say from this which one is greater. Not sufficient.

(1)+(2) \(y>0\) and \(x+y=1\) --> also insufficient: if \(x=0.1\) and \(y=0.9\) then the answer is NO but if \(x=0.9\) and \(y=0.1\) then the answer is YES.

Re: Is y – x positive? (1) y > 0 (2) x = 1 – y [#permalink]

Show Tags

06 Jul 2015, 01:40

Bunuel wrote:

satishreddy wrote:

Is y – x positive? (1) y > 0 (2) x = 1 – y

Is \(x-y>0\)? Or: is \(x>y\)?

(1) y>0. Clearly insufficient, as no info about \(x\). (2) x = 1 – y --> \(x+y=1\) --> the sum of two numbers equals to 1, we can not say from this which one is greater. Not sufficient.

(1)+(2) \(y>0\) and \(x+y=1\) --> also insufficient: if \(x=0.1\) and \(y=0.9\) then the answer is NO but if \(x=0.9\) and \(y=0.1\) then the answer is YES.

Answer: E.

Bunuel! The question asks if "y-x positive" i.e is y-x>0 ==> is y>x. But if you multiply both sides by -1 to reverse the equation you should flip a sign i.e x-y<0 ==> x<y. Is there a typo in your solution? Or i missed someting? Thanks!
_________________

(1) y>0. Clearly insufficient, as no info about \(x\). (2) x = 1 – y --> \(x+y=1\) --> the sum of two numbers equals to 1, we can not say from this which one is greater. Not sufficient.

(1)+(2) \(y>0\) and \(x+y=1\) --> also insufficient: if \(x=0.1\) and \(y=0.9\) then the answer is NO but if \(x=0.9\) and \(y=0.1\) then the answer is YES.

Answer: E.

Bunuel! The question asks if "y-x positive" i.e is y-x>0 ==> is y>x. But if you multiply both sides by -1 to reverse the equation you should flip a sign i.e x-y<0 ==> x<y. Is there a typo in your solution? Or i missed someting? Thanks!

Yes, the question asks whether y > x, while I wrote x > y. But this changes nothing in solution or answer.
_________________

Is y – x positive? (1) y > 0 (2) x = 1 – y [#permalink]

Show Tags

29 Nov 2017, 01:56

Is y – x positive?

(1) y > 0 - clearly insufficient (2) x = 1 – y

chetan2u, is my approach correct? If yes, is it safe to approach such problems in this manner? (Thank You ) statement 2: x = 1 – y adding -y on both sides

x-y = 1-2y if x-y is negative then y-x is positive.

case 1 :if y = 0,1,... , x-y is negative, y-x is positive case 2: if y= negative , x-y is positive, y-x is negative case 3: if 0<y<1, (x-y) is positive , y-x is negative

1 &2 => eliminates case2. still insufficient --E--
_________________

------------------------------ "Trust the timing of your life" Hit Kudus if this has helped you get closer to your goal, and also to assist others save time. Tq

chetan2u, is my approach correct? If yes, is it safe to approach such problems in this manner? (Thank You ) statement 2: x = 1 – y adding -y on both sides

x-y = 1-2y if x-y is negative then y-x is positive.

case 1 :if y = 0,1,... , x-y is negative, y-x is positive case 2: if y= negative , x-y is positive, y-x is negative case 3: if 0<y<1, (x-y) is positive , y-x is negative

1 &2 => eliminates case2. still insufficient --E--

Hi...

I think it's correct in this particular case....

Another look at the Q..

Combined.. x=1-y......x+y=1 and y>0 We do not know the relationship between x and y.. X could be >y, x=0.6 & y=0.4......x-y is positive x could be <y, x=0.4 & y=0.4........y-x is positive E
_________________